Gender relations, early childhood education and political changes in Brazil: Contributions to a state of the art - da Silva, Peterson Rigato [UNESP]; da Silva, Tassio José; Finco, Daniela (FapUNIFESP (SciELO), 2020)
To update an text published in 2006 (Faria), this article gathers studies on gender relations, conducted until 2016 and that are still rare in the field of early childhood education. These studies analyze the peer cultures and power relations among girls and boys up to 6 years old-both among the children, and between the children and teachers at daycare centers and preschools. In this process, the feminist struggle and studies of gender contribute substantially to modifications to early childhood education and to the construction of a non-sexist pedagogy.
Relações de gênero, educação da pequena infância e mudanças políticas no Brasil: Contribuições para um estado da arte*
Keywords: Daycare Center and Preschool; Early Childhood; Early Childhood Education; Feminist Movement; Gender Relations